The evolving international investment regime expectations, realities, options - Columbia International Investment Conference 2007 : Columbia University); Alvarez, Josâe E., 1955-; Sauvant, Karl P. (New York ; Oxford : Oxford University Press, 2011)
This title analyzes the existing challenges to the international investment regime, and addresses these challenges going forward. It also examines the dynamics of the international regime, as well as a broader view of the changing global economic reality both in the United States and in other countries.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Investments, Foreign -- Law and legislation -- Congresses